Politically connected firms and forward-looking disclosure in the era of Oman Vision 2040 - Hidaya Al Lawati (Journal of Risk and Financial Management, 2022)
Oman Vision 2040 is the blueprint for Oman's future aspirations. This vision is set with a number of high-level long-term targets to reflect the desired progress towards the strategic goals, in order to direct all Omani companies to build productive strategies and innovative plans to diversify the country's economy and reduce the dependence on the oil sector. All Omani companies are required to move according to this path by disclosing forward-looking information and goals in their annual reports. The progress will be monitored by the Vision 2040 Follow Up Unit which will report regularly on the targets. Therefore, our paper examines whether the presence of ruling family members on boards of directors impacts the quality and tone of forward-looking disclosure (FLD). Based on the sample of 34 Omani financial listed firms on Muscat Stock Exchange between 2014 and 2020, we found that there is a positive and significant association between politically connected firms and FLD quality. This confirms prior literature that politically connected firms are considered more transparent than their non-connected peers. We also found that firms with ruling family board members disclose more good forward-looking news in the chairman's statements. Furthermore, in the case of poor financial performance firms, we found that ruling members tend to disclose more good news than bad news, and they could use impression management techniques to avoid the negative attraction and to maintain their reputation in the market. From these findings, we draw important implications for policymakers and shareholders who need to encourage firms to appoint ruling family directors on their boards (to a specific extent) due to the potential beneficial outcomes they deliver.
Keywords: 650; forward-looking disclosure; Oman; politically connected firms; ruling family directors